PENGEMBANGAN GAMIFIKASI “DAKON EDUKATIF” MATERI KERAGAMAN BUDAYA UNTUK MENINGKATKAN SELF ESTEEM SISWA KELAS V SD DI UPT SD NEGERI MODANGAN 05 BLITAR - Azizaturrohmah Azizaturrohmah; Cindya Alfi; Ragil Tri Oktaviani (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study was motivated by the low self-esteem of fifth-grade students at UPT SD Negeri Modangan 05 Blitar in learning Science and Social Studies (IPAS) on cultural diversity material. This condition was indicated by their lack of confidence in expressing opinions, answering questions, and actively participating in learning activities. This study aimed to develop the Educational Dakon Gamification media, determine its validity and feasibility, and analyze the improvement of students' self-esteem. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of this study were 21 fifth-grade students. Data were collected through observations, interviews, and questionnaires, and then analyzed using validity, feasibility, and normalized gain (N-Gain) tests. The results showed that the Educational Dakon Gamification media was highly valid and feasible for use, with validation scores of 94% from material experts, 100% from media experts, and 100% teacher response. Student responses reached 92%, categorized as very good. The improvement in students' self-esteem was indicated by an N-Gain score of 0.79, falling into the high category. Therefore, the Educational Dakon Gamification media is effective in improving students' self-esteem in learning cultural diversity. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya self-esteem siswa kelas V UPT SD Negeri Modangan 05 Blitar pada pembelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) materi keragaman budaya. Kondisi tersebut ditunjukkan melalui kurangnya keberanian berpendapat, menjawab pertanyaan, serta berpartisipasi aktif dalam kegiatan belajar. Penelitian ini bertujuan untuk mengembangkan media gamifikasi dakon edukatif, mengetahui kevalidan dan kelayakannya, serta menganalisis peningkatan self-esteem siswa. Jenis penelitian ini menggunakan metode Research and Development (R&D) dengan model Analysis, Design, Development, Implementation, dan Evaluation (ADDIE). Subjek penelitian melibatkan 21 siswa kelas V sekolah dasar. Data dikumpulkan melalui observasi, wawancara, dan angket, kemudian dianalisis menggunakan uji valididad, kelayakan, serta normalized gain (N-Gain). Hasil penelitian menunjukkan media gamifikasi dakon edukatif sangat valid dan layak digunakan dengan hasil validasi ahli materi sebesar 94%, ahli media 100%, dan respon guru sebesar 100%. Respon peserta didik memperoleh persentase 92% dengan kategori sangat baik. Peningkatan self-esteem siswa ditunjukkan oleh nilai N-Gain sebesar 0,79 yang termasuk dalam kategori tinggi. Dengan demikian, media gamifikasi dakon edukatif efektif digunakan untuk meningkatkan self-esteem siswa pada pembelajaran materi keragaman budaya.